Experimental Studies on Fibre Integrated Lightweight Concrete Frames Under Lateral Forces: A Review - Muthulakshmi, M.; Vinod Kumar, M. (Asian Journal of Engineering and Applied Technology, 2018)
Reinforced Concrete (RC) framed structure with masonry infill is the most common type of building in which, RC frames participate in resisting lateral forces. The poor performance of RC frame buildings under lateral forces is due to its heavy mass and rigid construction. Use of Lightweight concrete (LWC) is preferred since the dead load of concrete is enormous. A low density of the LWC, decreases the weight of the building thus reducing the effect of lateral forces. However, LWC having a lower modulus of elasticity, has a faster rate of crack development in RC members. So, fibres are employed as an additive to increase the energy absorption capacity and to control the crack development. Pumice is a natural material of volcanic origin, has low density, which makes it ideal for production of LWC. Based on these ideas, Pumice aggregate is used as a partial replacement of coarse aggregate to its volume with addition of steel fibres to the volume of concrete. This paper summarizes the collected literatures related to RC frames, LWC, Fibre Reinforced Concrete (FRC) and thereby attempts to predict the lateral load response of RC portal frame with the use of LWC and Steel fibres.